PERANCANGAN SISTEM INFORMASI PEMESANAN KATERING BERBASIS WEB PADA WARTEG MITA JAYA - Camelia Evionita Zen (2022)
Warteg Mita Jaya is a typical Tegal restaurant that provides services in the food sector, one of which is catering. Currently the catering order process at Warteg Mita Jaya is still done manually, customers must come directly to the place to make an order transaction. This causes ordering activities not to run effectively and efficiently. The design of a website-based catering ordering information system is used to make it easier for customers to make transactions without having to come directly to where the caterer is located. The system development method used in this research is the waterfall method. The waterfall method is a method that is carried out sequentially. In the ordering system the author uses UML and MYSQL diagrams in processing data and this application is built using the HTML and PHP programming languages, MySQL as the database server. The result of this research is a computerized catering ordering information system and the system can accommodate sales data. After this ordering system research has been developed, the author hopes to make it easier for caterers to manage sales data and make it easier for consumers to make catering order transactions.